Implementation of TOPSIS Method in the Selection of Candidates for the Student Skills Competition in Technical Competence Drawing Building - Juanda Hakim Lubis; Mesran Mesran; Garuda Ginting; Zahri Hubby Ramadhani; Delvi Syahfitri (STMIK Budi Darma, 2021)
The selection of prospective participants in the student skills competition is a prestigious event for all students who attend Vocational High Schools throughout Indonesia, a prospective LKS is tasked with providing the results of a job in the competence of the competition being contested.The selection of the expected LKS candidates is not easy, because the decision to accept or not LKS candidates is still carried out in the old way, namely based on the selection of teachers in the competency areas being contested. This results in inaccurate selection decision making and the results are not appropriate and not on target, for that a decision support system is needed that will later assist decision making. Decision support system with application of methodTechnique for Others Reference by Similarity to Ideal Solution (TOPSIS) It is very much needed in order to be able to help make the right decisions in determining the selection of prospective student skills competitions (LKS) on building drawing engineering competencies. Technique For Others Reference by Similarity to Ideal Solution is a multi-criteria decision-making method or alternative choice which is an alternative that has the smallest distance from the positive ideal solution and the largest distance from the negative ideal solution from a geometric point of view by using distance.TOPSIS is known that from 3 three students the higher preference value is 0.8846, so that the result of the best student selection decision is the 2nd student. and accurate so that the resulting information can be used as decision support.